The overlap of symptomatic dimensions between frontotemporal dementia and several psychiatric disorders that appear in late adulthood - Pose, María Ángeles (2013)
Several factors make diagnosis of a possible behavioural variant of frontotemporal dementia (bvFTD) particularly challenging, especially the overlap of certain symptomatic dimensions such as apathy, disinhibition, depression, anhedonia, stereotyped behaviour, and psychosis between bvFTD and several psychiatric disorders that appear in late adulthood. We discuss the most frequent psychiatric conditions that can simulate early bvFTD symptoms, including late onset bipolar disorder, late onset schizophrenia-like psychosis, late onset depression, and attention deficit hyperactivity disorder in middle and older age.